Surgical quadriceps lengthening can reduce quadriceps spasticity in chronic stroke patients. A case-control study - Merlo, Andrea; Galletti, Martina; Zerbinati, Paolo; Prati, Paolo; Mascioli, Francesca; Basini, Giacomo; Rambelli, Chiara; Masiero, Stefano; Mazzoli, Davide (Frontiers in Neurology, 2022)
Background: Muscle overactivity is one of the positive signs of upper motor neuron lesions. In these patients, the loss of muscle length and extensibility resulting from soft tissue rearrangement has been suggested as a contributing cause of muscle overactivity in response to stretching. Objective: To assess the effects of surgical lengthening of the quadriceps femoris (QF) muscle-tendon unit by aponeurectomy on muscle spasticity. Methods: This is a case-control study on chronic stroke patients with hemiparesis that have undergone lower limb functional surgery over a 8-year period. CASEs underwent corrective surgery for both the foot and knee deviations, inclusive of a QF aponeurectomy. Controls (CTRLs) underwent corrective surgery for foot deviations only. QF spasticity was assessed with the Modified Tardieu Scale (MTS) before and one month after surgery. The Wilcoxon test was used to assess MTS variations over time and the Mann–Whitney test was used to verify the presence of group differences at the 1-month mark. Results: Ninety-three patients were included: 57 cases (30F, 1-34 years from lesion) and 36 controls (12F, 1-35 years from lesion). Before surgery, both CASEs and CTRLs had similar MTS scores (median MTS=3) and functional characteristics. One month after surgery, QF spasticity was significantly lower in the CASEs compared to CTRLs (p=0.033) due to a significant reduction of the median MTS score from 3 to 0 in the CASE group (p < 0.001) and no variations in the CTRL group (p = 0.468). About half of the cases attained clinically significant MTS reductions and complete symptom relief even many years from the stroke. Conclusions: Functional surgery inclusive of QF aponeurectomy can be effective in reducing or suppressing spasticity in chronic stroke patients. This is possibly a result of the reduction in neuromuscular spindle activation due to a decrease in muscle shortening, passive tension, and stiffness.